Development of three phase induction motor controller - Ahmad Fakhruzzaman, M Zawawi (2009)
The development of induction motor controller project is a part of three phase induction motor control system that will be designed based on microcontroller using MC68HC908MR32 integrated circuit manufactured by Motorola. This controller board is an integral part of embedded motion control series and will be interface with power circuit stage, optoisolator and emulator as one system to control a three phase induction motor speed by controlling the PWM output using microcontroller program. The controlled PWM output then will be transfer to power circuit board that consist of power inverter switching to control the speed of the three phase motor. This method is called V/F control method. This control board is equipped with overcurrent circuit sensor to detect fault for safety purpose and tachometer circuit to sense motor speed. This control board also have forward/reverse switch, start/stop switch and speed control pot.